Hubungan Faktor Lingkungan dan Perilaku Reseptivitas terhadap DBD (Demam Berdarah Dengue) di Wilayah Kerja Puskesmas Cijagra Lama Bandung Tahun 2023 - Nadeak, Yunita Sarah; Pardede, Eva Efrida; Basry, Stevani (Jurnal Riset Hesti Medan, 2023)
DHF is an infectious disease that is still a public health problem in the world, including Indonesia. Every year more than 700 million people worldwide are infected with the Dengue Virus and more than 2,000,000 people die. Most cases are in Africa and several Asian countries, Latin America, the Middle East and several parts of Europe. In Southeast Asia, in 20021-2022 it was reported that the incidence of DHF (Dengue Hemorrhagic Fever) was around 2,30-3,052,000 cases and deaths around 2,213-6,678 per year. Indonesia has a large number of dengue fever incidents (Dengue Hemorrhagic Fever) with the third highest position, with the number of confirmed cases of 229,819 reported cases and 432 deaths (WHO, 2020 in Ariati, et al, 2021). Problem Formulation The problem in this research is how environmental and behavioral factors relate to the receptivity of DBD (Dengue Hemorrhagic Fever) in the working area of the Cijagra Lama Bandung Public Health Center in 2023. The theoretical framework in this research is summarized based on a review of existing theories, specifically the type of this research is research observational using analytical methods with a cross sectional approach, namely measuring the dependent variable and independent variables simultaneously (Chandra, 2022) regarding the relationship between environmental and behavioral factors and receptivity to DBD (Dengue Hemorrhagic Fever). The population in this study were all 734 heads of families (KK) in 10 villages in the working area of the Cijagra Lama Bandung Community Health Center in 2023. From the results of research and analysis carried out regarding the relationship between environmental factors and behavioral factors with receptivity to DHF (Dengue Hemorrhagic Fever). ) in the working area of the Cijagra Lama Bandung Public Health Center in 2017, it can be concluded as follows: The majority of receptivity for DHF (Dengue Hemorrhagic Fever) is 71.9% and the density of larvae is 2.31%. The majority of environmental factors are unfavorable at 57.3%. the behavior of the majority was not good as much as 68.5%. There was a relationship between environmental factors and receptivity for DHF (Dengue Hemorrhagic Fever) (p = 0.000), There was a relationship between behavioral factors and receptivity for DHF (Dengue Hemorrhagic Fever) (p = 0.000).